Ոստիկանի անձի մասնագիտական կարևոր որակների փորձագիտական գնահատում - Նաիրա Նազարյան (ՀՀ ԳԱԱ հրատ.)
The aim of this work is to point out the most important professional qualities of the police personality based on the results of the expert judgement. It is accepted in psychology to measure the different aspects of professional success through the method of expert judgement and to decide the parameters of the activity estimation.
Keywords: Psychology